DETERMINAN FAKTOR KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pengguna Shopee Di Kota Yogyakarta) - Wahyu Ningsih, Wahyu Ningsih; Suhartono, Suhartono (Unitri Press, 2024)
Purpose: The aim of this research is to explain the impact of price discounts, e-service quality and electronic word of mouth on purchasing decisions through consumer trust as an intervening variable for Shopee users in the city of Yogyakarta, Methods: this research uses quantitative methods by distributing questionnaires. The sample obtained was 115 respondent. Data analysis: using descriptive data analysis techniques and path analysis, Result and discussions: the results of the regression coefficient were interpreted so that the positive influence of the four variables showed that sales would increase by 0.143 items when the added value of the price discount variable increased by one element. Sales increased by 0.046 items for every increase in e-service quality elements. Sales increased 0.448 for every point increase in the e-wom variable value. Sales increased 0.219 for every point increase in the value of the consumer trust variable, Conclusion: Price discount, e-service quality and e-wom have a positive and significant effect on consumer trust in Shopee users in the city of Yogyakarta. Price discount and e-service quality have no positive effect and significance towards purchasing decisions among Shopee users in the city of Yogyakarta, while e-wom and consumer trust have a positive and significant influence on purchasing decisions among Shopee users in the city of Yogyakarta, and consumer trust is able to mediate price discounts, e-service quality and e-wom towards purchasing decisions for Shopee users in the city of Yogyakarta.